Development of a User-Friendly Graphic Tool to Estimate Individualized Survival Curves for Advanced Cancer Patients in Hospice Care. Issue 1 (March 2015) - Chiang, Jui-Kun; Koo, Malcolm; Kao, Yee-Hsin
This prospective study aimed to develop an individualized prognostic tool for predicting the survival probability at any given point for a hospice patient with advanced cancer. A total of 286 patients with advanced cancer were included in the study. Median observational time was 18 days (range: 1 to 60 days). Cox proportional hazards regression analysis revealed that faster heart rate (hazard ratio [HR]=1.01), jaundice (HR=2.32), poorer performance status (HR=2.01), and antifungal treatment (HR=1.62) were independent predictors of shorter survival time. Patients with infections who received aminoglycoside treatments (HR=0.45) were associated with longer survival times. Based on this model, we could construct a covariate-adjusted individualized survival curve for a given patient according to his or her clinical condition. This user-friendly tool for estimating the survival probability of patients with advanced cancer in hospice settings could facilitate clinical decision making and medical care planning.